2007
DOI: 10.1002/mds.21865
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in Parkinson's disease: Analysis of behavioral and physiological patterns in the Iowa gambling task

Abstract: Recent studies suggest that social recognition processes are affected by Parkinson's disease (PD). However, whether PD patients exhibit behavioral changes is still controversial. The purpose of the present study was to examine the decision making of PD patients performing the Iowa Gambling Task (IGT). We recruited a large number of early, nondemented PD patients for the IGT. We also recorded the skin conductance responses (SCRs) during the task as a measure of emotional arousal. Compared with the normal contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
100
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 35 publications
12
100
1
6
Order By: Relevance
“…Neuroimaging studies on healthy subjects (HS) showed that the activated regions during IGT were those underlying both somatic activation and future oriented decisionmaking [7]. However, recent reports showed the complexity of this task that might also be considered as a measure of risk taking [1,[8][9][10][11]. In particular, poor performance during the first part of the task has been related to ambiguous risk taking [12][13][14][15].…”
Section: Cognitive Impulsivitymentioning
confidence: 99%
“…Neuroimaging studies on healthy subjects (HS) showed that the activated regions during IGT were those underlying both somatic activation and future oriented decisionmaking [7]. However, recent reports showed the complexity of this task that might also be considered as a measure of risk taking [1,[8][9][10][11]. In particular, poor performance during the first part of the task has been related to ambiguous risk taking [12][13][14][15].…”
Section: Cognitive Impulsivitymentioning
confidence: 99%
“…maximize one's profits. Some have shown that PDs' overall winnings are substantially less than HCs, as indicated by failure to select the advantageous deck (Czerneki et al, 2002;Kobayakawa et al, 2008;Mimura et al, 2006). But, others have shown that the overall success in maximizing earnings is equivalent in both HCs and PDs (Euteneuer et al, 2010;Poletti, et al, 2010;Thiel et al, 2003).…”
Section: Iowa Gambling Task (Igt)mentioning
confidence: 99%
“…The SCR patterns were compared with those of 12 age-matched normal controls. The procedures are described in detail in an earlier study [13]. …”
Section: Methodsmentioning
confidence: 99%
“…Although decision-making [12,13] and facial expression recognition [14,15,16] are social cognitive skills that are known to be impaired in PD, no studies have been conducted to date on decision-making in RBD. Furthermore, our case study focused on whether these cognitive symptoms, autonomic dysfunction, and abnormal dopamine metabolism appear in a particular order.…”
Section: Introductionmentioning
confidence: 99%